The association between grip strength and isometric mid-thigh pull performance in elite footballers - Rhodes, D.; Jeffery, J.; Carling, C.; Alexander, J. (Science & Sports, 2022)
Objectives The purpose of the present study was to analyse the association between grip strength and performance of the standardised protocol of the isometric mid-thigh pull (IMTP) test. Methods In total, 31 elite premier league footballers completed test-retest measures of peak force (PF) grip strength and IMTP, measures were taken 7 days apart. Post-completion of the test-retest 3 maximal IMTP and bilateral grip strength measures were taken. Mean PF was calculated bilaterally for each assessment. Linear relationships were determined for test-retest and Grip Strength Test (GST) and IMTP PF output. Results Test-retest of the GST and IMTP displayed significant almost perfect correlations bilaterally (P = 0.001, r = 0.92-0.94, CI = 0.85-0.96). Bilateral moderate-large significant correlations were also identified between grip strength and IMTP PF (P = 0.05, r = 0.54-0.72, CI = 0.30-0.86). Conclusions GST and IMTP are reliable and repeatable measures. Findings in the present study indicate consideration must be given to the influence of grip strength on maximal IMTP PF output. Previous literature describes standardisation procedures for IMTP performance. Pre-completion of IMTP measures in elite footballers, performance practitioners should consider assessment of the athlete's grip strength despite the use of lifting straps.